Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3758/s13423-015-0935-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between attention allocation and cheating

Abstract: Little is known about the relationship between attention allocation and dishonesty. The goal of the present work was to address this issue using the eyetracking methodology. We developed a novel task in which participants could honestly report seeing a particular card and lose money, or they could falsely report not seeing the card and not lose money. When participants cheated, they allocated less attention (i.e., shorter fixation durations and fewer fixations) to the card than when they behaved honestly. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
3
21
0
1
Order By: Relevance
“…Another related example, adopted by Pittarello et al . (), involves indicating when a certain card suit appears on a screen.…”
Section: Method: How Do We Study Dishonesty?mentioning
confidence: 99%
See 2 more Smart Citations
“…Another related example, adopted by Pittarello et al . (), involves indicating when a certain card suit appears on a screen.…”
Section: Method: How Do We Study Dishonesty?mentioning
confidence: 99%
“…Bounded ethicality theory suggests that, in fact, people often do not recognize that they are acting immorally in the decision moment or they strategically avoid processing the fact that the choice might be unethical. Recently, eye‐tracking tools have been introduced to study whether bounded ethicality and moral blind‐spot strategies are physically used to lie and misbehave (Pittarello et al ., ). People seem to strategically avoid looking at information that will prevent them from being able to tell a self‐serving lie (Pittarello et al ., ).…”
Section: Summing Up: Does the Evidence Support The Theory?mentioning
confidence: 97%
See 1 more Smart Citation
“…In a lab experiment on dishonesty, Pittarello et al (2016) showed participants two cards from a deck and asked them to indicate whether one of the cards was a Joker. Each time they reported a Joker, they lost EUR 1 from their endowment of EUR 60.…”
Section: Avoiding Projection Biasesmentioning
confidence: 99%
“…Active and passive transgressions are treated differently by the law (Feinberg, 1984) and are judged and weighed differently by spectators (e.g., Baron & Ritov, 2004;Spranca, Minsk, & Baron, 1991), producing different effects of social desirability. For instance, participants are more likely to serve their self-interest by refraining from telling the truth (lie of omission) than by deliberately lying (lie of commission) when they face the temptation to benefit from dishonesty (Pittarello, Motro, Rubaltelli, & Pluchino, 2016).…”
Section: Measures the Omission As A Compromise On Moral Foundations Smentioning
confidence: 99%